Synthesis of 1-Carboxamido-3,5-Diaryl-Δ2-Pyrazolines and Their Antimicrobial Study - Kedar, R.M. (Asian Journal of Chemistry, 2010)
Nine chalcones were obtained by condensing acetophenones with aromatic aldehydes in ethanolic NaOH. Their structures were confirmed by physical as well as chemical methods. These chalcones were then reacted with semicarbazide hydrochloride in presence of aqueous alkali in ethanol to get 1-carboxamido-3,5-diaryl- Δ2-pyrazolines. The structures of these compounds were established on the basis of chemical properties and spectral analysis. These compounds were subjected to antimicrobial tests against the test organisms: Klebsiella pneumoniae, Escherichia coli, Proteus mirabilis, Staphylococcus aureus, Shigella dysentery and Salmonella typhi. It has been found that the compounds containing chloro and dimethylamino groups as substituents enhance the antimicrobial activity.